O papel criativo do juiz na colisão entre os direitos fundamentais à vida privada e à liberdade de expressão e de comunicação - Vilande, Fernanda Carravetta (Universidade do Vale do Rio do Sinos, 2006)
The declaratory jurisdiction of law conception is exceeded, not suitable to the Democratic State of Law, where the judge is an effective creative agent, although it’s still possible to glimpse a contradiction between the theoretical common direction of the jurists and the new posture of the Judiciary Power and the law operators. Such can be observed in the current use of the interpretative methods, that, under pretense objectivity, culminates for covering with arbitrariness interpretative activity, being important to take a look under the prism of Gadamer’s and Heidegger’s philosophical hermeneutics, where the interpretative process is unique, in which the understanding-interpretation-application happens at the same time.With this horizon, the fundamental rights to the private life and the liberty of expression and communication are examined, both expressions of the principle of the dignity of the person human being, central value of the legal system. The cited fundamental rights very frequently collide betwe
Keywords: colisão; criação judicial; direitos fundamentais; liberdade de comunicação; liberdade de expressão; privacidade; privacy; collision; fundamental rights; judicial creation; liberty of communication; liberty of expression; Ciências Sociais Aplicadas